2013
DOI: 10.2174/09298673113209990144
|View full text |Cite
|
Sign up to set email alerts
|

Xanthones as Potential Antioxidants

Abstract: Xanthones (dibenzo-γ-pyrones) constitutes an important class of oxygenated heterocycles and occur as secondary metabolites in plants and microorganisms. They are known for various biological activities such as antioxidant, monoamine oxidase inhibitor, antihypertensive, hepatoprotective, antithrombotic, antifungal and anticancer. The tricyclic scaffold as well as the nature and/or position of the substituents present on it play an important role in displaying various biological activities. The unique structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 0 publications
0
49
0
1
Order By: Relevance
“…Polygala japonica ), the attention they have received is not the same. Whereas some studies have analyzed the structure–activity relationships of antioxidant flavonoids, there are none that have focused on the structure–activity relationships of antioxidant xanthones.…”
Section: Introductionmentioning
confidence: 99%
“…Polygala japonica ), the attention they have received is not the same. Whereas some studies have analyzed the structure–activity relationships of antioxidant flavonoids, there are none that have focused on the structure–activity relationships of antioxidant xanthones.…”
Section: Introductionmentioning
confidence: 99%
“…Xanthones and flavonoids are important sources of phenolic antioxidants. Sometimes, they co‐exist in the same medicinal plant (especially Chinese herbal medicine) ,. Their frameworks are quite different, however, in the flavonoid framework, there is a σ ‐bond between the B ring and A/C fused‐ring, and the rotation around this σ ‐bond can form different three‐dimensional configurations.…”
Section: Figurementioning
confidence: 99%
“…An in‐depth analysis suggested that the catechols in the xanthone family could be further divided into three types: 6,7‐catechol, 1,2‐catechol (or 7,8‐catechol), and 5,6‐catechol types ,,. For example, six xanthones ( 1, 2, 3, 4, 6 , and 15 ).…”
Section: Figurementioning
confidence: 99%
“…The pharmacological properties of both natural and synthetic xanthones (e.g., anti-inflammatory, antimalarial, antioxidant, and antitumour activities) are associated to different substituents in different positions of their main core [7][8][9][10][11][12]. Aryl groups linked to xanthones are scarce in natural sources, but several publications reporting their synthesis and/or biomedical potential have been highlighted in literature and reviewed in [13].…”
Section: Introductionmentioning
confidence: 99%